A Comprehensive Review on Importance and Quantitation of Atypical Antipsychotic Drugs and their Active Metabolites in Commercial Dosage Forms - Rahman, Habibur; Haque, S.K. M.; Siddiqui, Masoom Raza (Current Pharmaceutical Analysis, 2020)
Background: Schizophrenia is a severe mental illness that affects more than twenty-one million people throughout the world. Schizophrenia also causes early death. Schizophrenia and other related psychotic ailments are controlled by the prescription of antipsychotic drugs, which act by blocking certain chemical receptors in the brain and thus relieves the symptoms of psychotic disorder. These drugs are present in the different dosage forms in the market and provided in a certain amount as per the need of the patients. Objective: Since such medications treat mental disorders, it is very important to have a perfect and accurate dose so that the risk factor is not affected by a higher or lower dose, which is not sufficient for the treatment. For accurate assay of these kinds of drugs, different analytical methods were developed ranging from older spectrophotometric techniques to latest hyphenated methods. Results: The current review highlights the role of different analytical techniques that were employed in the determination and identification of antipsychotic drugs and their metabolites. Techniques such as spectrophotometry, fluorimetry, liquid chromatography, liquid chromatography-mass spectrometry, gas chromatography, and gas chromatography-mass spectrometry employed in the method development of such antipsychotic drugs were reported in the review. Different metabolites, identified using the hyphenated techniques, were also mentioned in the review. The synthesis pathways of few of the metabolites were mentioned. Conclusion: The review summarizes the analyses of different antipsychotic drugs and their metabolites. A brief introduction of illnesses and their symptoms and possible medications were highlighted. Synthesis pathways of the associated metabolites were also mentioned.
Keywords: hyphenated methods